Gelatin-Thrombin Matrix: A New and Simple Way to Manage Recurrent Epistaxis in Hematology Units. (23rd May 2013) - Buiret, G.; Pavic, M.; Pignat, J. C.; Pasquet, F.
Abstract : Introduction . In case of thrombopenia and/or thrombopathy, epistaxes are very difficult to manage. Case Series . Two patients, one with a thrombocytopenia, the other with a thrombopathy, were hospitalized because of repeated active epistaxes after failure of packing. Both patients were successfully treated with an application of Surgiflo without side effects and left the hospital without recurrence of epistaxis. Discussion . Being a subject of many studies dealing with epistaxis, Surgiflo is a simple treatment that seems to be very effective and without side effects to treat acute epistaxis in fragile patients with coagulation disorders. Prospective studies of tolerance and efficiency in such situations should be performed.